Microstructure evolution of 316L stainless steel during solid-state additive friction stir deposition. Issue 7 (3rd April 2022) - Beladi, Hossein; Farabi, Ehsan; Hodgson, Peter D.; Barnett, Matthew R.; Rohrer, Gregory S.; Fabijanic, Daniel
ABSTRACT: Solid-state additive friction stir deposition was employed to three dimensionally print a 316L stainless steel. The microstructure, texture and grain boundary distribution were characterised using five-parameter boundary analysis. The bulk microstructure was exceptionally fine (∼0.7 µm) throughout the thickness of the deposited layers, consisting of equiaxed grains along with sub-grains delineated by high and low angle boundary segments. The misorientation angle distribution of the deposited layers was considerably different from the as-received microstructure, exhibiting a significant reduction in the relative areas of ∑3 annealing twin boundaries due to their distortion by severe plastic deformation. The overall texture also exhibited strong shear components associated with FCC metals, suggesting that the microstructure refinement largely took place through progressive subgrain rotation, known as continuous dynamic recrystallisation. The grain boundary plane distribution revealed significantly lower anisotropy compared with the as-received material, showing two moderate peaks at the (111) and (110) orientations. The migration of high-angle mobile boundaries, which may have been induced by thermal cycle upon subsequent deposition along with the dislocation gradients between adjacent grains, slightly enhanced the intensity of low energy (111) orientations at the expense of (110) high-energy boundaries.